The Image of Mother in Ukrainian Folk Tales - Ptashchuk, Iryna (Pedagogical Discourse, 2014)
The article justifies the use of Ukrainian folk tales as an effective means of educating. This article also discusses the influence of folklore on the formation of the women’s responsible attitude to motherhood. By the specific examples the educational potential of Ukrainian folk tales in terms of the formation of future mothers correct vision of the world and themselves in it is investigated. Attention is paid to the fact that folklore reflects emotional and esthetic, artistic, creative, moral and intellectual potential of the Ukrainian people and creates conditions for the growth and development of natural instincts and talents of every citizen of Ukraine. The examples of traditional Ukrainian folk types of fantasy characters: mother, mother nature and the evil stepmother are considered and analyzed. In conclusion the article summarizes the opinion that vivid image of the mother in the tales promotes correct and timely formation of girls purely maternal features of character and personality traits: hard work, patience, love of children, the ability to keep house, cleanliness, kindness, maintaining high moral norms of behavior, etc.